ҚАРАҚАЛПАҚ ТОЙ МӘРЕСИМИ ҲӘМ ОҒАН БАЙЛАНЫСЛЫ ДӘСТҮРЛЕРДИҢ ЕРТЕК ТИЛИНДЕ СӘЎЛЕЛЕНИЎИ - Кунназарова, Ш.М. (FAN va JAMIYAT, 2019)
The article is devoted to the analysis of wedding ceremonies and traditions in folk fairy-tales from the point of view of linguoculturology. The author has done the comparative study of wedding ceremonies and traditions in fairy-tales and other genres of folklore.